Social protection responses to COVID-19 in MENA: Design, implementation and child-sensitivity - Charlotte Bilo; Jo\~ao Pedro Dytz; Lucas Sato (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
COVID-19 has affected all countries in the Middle East and North Africa (MENA) region, and groups already vulnerable before the crisis, such as children, have been particularly affected. Social protection can promote children's well-being and reduce the negative impacts of crises on them, especially if their needs and vulnerabilities are taken into account. Against this background, the IPC-IG and UNICEF MENARO partnered to analyse the social protection responses to COVID-19 in MENA and assess the extent to which they took children's needs into account.
Keywords: 330; child-sensitive social protection; programme design; MENA